233 Effects of Harvest Maturity And/or Kernel Processing on Corn Silage Processing Score and Particle Size of Corn Silage. (7th May 2021) - Hamilton, Thomas; Walker, Julie; Rusche, Warren C; Smith, Zachary K
Abstract: A single corn hybrid was used to evaluate harvest maturity (Mat) and/or kernel processing (KP) effects on corn silage processing score (CSPS) and particle size (PS). Treatments were arranged in a 2 × 2 factorial of 1) Mat (early and late) and 2) KP (no or yes). A single corn field was planted on April 27, 2020. There were 12 loads (experimental unit) per simple effect treatment mean. Data were analyzed as a completely randomized design. Early harvest occurred on August 28, 2020 [yield (as is) = 39.1 Mg/hectare; DM = 43.1%; CP, NDF, and starch = 6.5, 46.0, and 32.9%, respectively (DM basis)]. Late harvest occurred on September 9, 2020 [yield = 37.8 Mg/hectare (as is); DM = 49.2%; CP, NDF, and starch = 6.6, 49.8, and 37.5%, respectively (DM basis)]. The same equipment was used for both Mat with KP achieved by narrowing processing rollers. The CSPS was determined as the proportion of starch retained below a 4.75-mm sieve. Grain content (DM basis) of the corn silage was calculated from starch/0.72. Particle size was assessed using the Penn State Particle Separator. A Mat × KP interaction (P = 0.05) was detected for CSPS. Early/no and late/no had decreased (P ≤ 0.05) CSPS compared to early/yes and late/yes had the greatest CSPS (P ≤ 0.05) compared to others. Grain content was 13.9% greater in late compared to early (P = 0.01). A Mat × KP interaction (P = 0.03) was detected for PS. Early/no had the greatest (P ≤ 0.05) PS, early/yes and late/no were intermediate, and late/yes had decreased PS compared to others (P ≤ 0.05). These data indicate that Mat and KP influence CSPS synergistically. Producers should consider KP when corn silage is harvested at a later maturity to enhance CSPS.